Cancer and Risk of COVID‐19 Through a General Community Survey. (7th September 2020) - Lee, Karla A.; Ma, Wenjie; Sikavi, Daniel R.; Drew, David A.; Nguyen, Long H.; Bowyer, Ruth C. E.; Cardoso, M. Jorge; Fall, Tove; Freidin, Maxim B.; Gomez, Maria; Graham, Mark; Guo, Chuan‐Guo; et al.
Abstract: Individuals with cancer may be at high risk for coronavirus disease 2019 (COVID‐19) and adverse outcomes. However, evidence from large population‐based studies examining whether cancer and cancer‐related therapy exacerbates the risk of COVID‐19 infection is still limited. Data were collected from the COVID Symptom Study smartphone application since March 29 through May 8, 2020. Among 23, 266 participants with cancer and 1, 784, 293 without cancer, we documented 10, 404 reports of a positive COVID‐19 test. Compared with participants without cancer, those living with cancer had a 60% increased risk of a positive COVID‐19 test. Among patients with cancer, current treatment with chemotherapy or immunotherapy was associated with a 2.2‐fold increased risk of a positive test. The association between cancer and COVID‐19 infection was stronger among participants >65 years and males. Future studies are needed to identify subgroups by tumor types and treatment regimens who are particularly at risk for COVID‐19 infection and adverse outcomes. Abstract : Patients with cancer may be at a higher risk for COVID‐19; however, supporting evidence from large population‐based studies is still limited. This study examined whether incidence of infection is higher in individuals with cancer.